Digital citizenship in the AI Era: Ethical and pedagogical challenges from Muhammadiyah values perspective - Tutik Wijayanti; Masrukhi Masrukhi; Daffa Fakhri Maulana; Hendri Irawan (Kuras Institute, 2026)
Purpose − The rapid development of Artificial Intelligence (AI) has transformed digital citizenship by reshaping civic participation, public discourse, and democratic interaction in digital spaces. Alongside broader opportunities for civic engagement, AI also raises ethical challenges such as algorithmic bias, disinformation, social polarization, privacy violations, and the decline of citizens’ critical-reflective capacities. This study aims to examine the ethical and pedagogical challenges of digital citizenship education in the AI era and to explore Muhammadiyah values as a religious-ethical framework for fostering ethical digital citizenship. Method − This study employed a qualitative library research approach. Data were collected from journal articles, academic books, policy documents, and official publications related to AI, digital citizenship, and Muhammadiyah thought. The data were analyzed using content analysis and conceptual–normative analysis guided by Muhammadiyah values, including aqidah, akhlak, ibadah, and muamalah duniawiyah within the paradigm of Progressive Islam. Findings − The findings reveal that AI fundamentally transforms digital citizenship through the mediation of information flows, participation patterns, and public opinion formation. Although AI expands civic engagement opportunities, it also creates ethical risks that may weaken democratic values and social responsibility. Muhammadiyah values provide a relevant ethical foundation for strengthening digital citizenship education by promoting critical awareness, moral responsibility, and ethical participation in digital spaces.